RETRACTED: Numerical investigation of multiphase flow in a channel - Salomov Uktam; Madaliyev Murodil; Kuchkarov Akmaljon (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001